(untitled) (Comprehensive Journal of Science, 2026)
Human resource performance evaluation is a continuous and structured process that yields numerous benefits for both the organization and its employees. However, this process relies on a standardized model for evaluating the performance of all jobs. This standardized model has revealed clear shortcomings in evaluating administrative, technical, and other functions and activities. This study aims to identify the performance evaluation criteria used in the standardized model and propose several alternative models for evaluating human resource performance at Eni Oil Company. These alternative models would allow for the analysis of individual capabilities and efforts, enabling informed decisions regarding their career paths. The study employed a descriptive methodology using exploratory research by analyzing relevant data and information. Among its key findings are that the criteria used in the standardized model lack a high degree of accuracy and that the evaluation is based on overall performance rather than on the specific tasks completed. The study concludes with several recommendations, most notably the proposal of several specialized models for evaluating different job functions.